2017
DOI: 10.3923/jms.2017.95.101
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Assessment of the Effect of Chewing Qat on Hemodynamics of the Common Carotid Arteries

Abstract: is an International, peer-reviewed scientific journal that publishes original article in experimental & clinical medicine and related disciplines such as molecular biology, biochemistry, genetics, biophysics, bio-and medical technology. JMS is issued four times per year on paper and in electronic format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…They found that the RI and PI were significantly lower after chewing khat. [ 10 ] They studied the influence for 2 h before and after chewing khat. In contrast, the RI and PI in the current study increased significantly due to the long-term use of khat for several years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the RI and PI were significantly lower after chewing khat. [ 10 ] They studied the influence for 2 h before and after chewing khat. In contrast, the RI and PI in the current study increased significantly due to the long-term use of khat for several years.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the PSV and EDV increased after chewing khat. [ 10 ] The elevation of blood flow velocity might be attributed to increased HR and BP as a consequence of chewing khat. Abnormal carotid flow velocities and pulsatility may be associated with cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow velocities were increased and the Doppler indices were decreased when assessing the immediate effect of Khat chewing on Doppler hemodynamics of common carotid arteries (Ibrahim et al, 2017). Doppler ultrasonography scan is non-invasive and appropriate for the bedside examination.…”
Section: Introductionmentioning
confidence: 98%
“…With the measuring of flow volumes in the carotid arteries (CAs), this technique has been used to detect extracerebral blood flow among healthy populations. Doppler's indices; resistive index (RI) and pulsatility index (PI) are common parameters for characterizing the waveform to translate the vascular resistance (Ibrahim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%